Generalized collective modes approach: Mode contributions to time correlation functions in liquid lead - Bryk, T.; Mryglod, I. (Condensed Matter Physics, 2001)
Contributions of different collective excitations to the density-density and heat-heat time correlation functions in pure liquids are studied within an approach of generalized collective modes. It is shown, that a kinetic relaxing mode, caused by slow density fluctuations, defines almost completely the shape of density-density time correlation function for wavenumbers close to the main peak position of the static structure factor. Analytical threevariable model is used to explain negative amplitudes of contributions to dynamical structure factor from short-wavelength excitations. Such contributions can appear in the range of wavenumbers close to the main peak position of static structure factor.